Cognitive and Neuropsychiatric Symptom Differences in Early Stages of Alzheimer’s Disease: Kuopio ALSOVA Study - Ilona Hallikainen; Anne M. Koivisto; Teemu Paajanen; Asta Hiltunen; Pertti Karppi; Matti Vanhanen; Tarja Välimäki; Sanna-Kaisa Herukka; Hilkka Soininen; Tuomo Hänninen (Dementia and Geriatric Cognitive Disorders Extra, 2012)
Background/Aim: Alzheimer’s disease (AD) causes impairment in memory and other cognitive functions as well as neuropsychiatric symptoms and limitations in the activities of daily living (ADL). The aim of this study was to examine whether demographic variables, dementia severity, ADL and neuropsychiatric symptoms are associated with cognition in very mild or mild AD. Methods: We analyzed the baseline data of 236 patients with very mild or mild AD participating in a prospective AD follow-up study (ALSOVA). The Consortium to Establish a Registry for Alzheimer’s Disease neuropsychological battery total score was used in the evaluation of the global cognitive performance. Results: Cognition was associated with dementia severity and ADL but not with neuropsychiatric symptoms. ADL functions were associated with both cognitive performance and neuropsychiatric symptoms. Conclusion: Even patients with very mild or mild AD may exhibit neuropsychiatric symptoms not related to cognitive impairment. The results of this study emphasize the importance of taking a multidimensional approach to the diagnostic and prognostic evaluation of AD patients already in the early stages of the disease.